Cognitive-Behavioral Strategies to Increase the Adherence to Exercise in the Management of Obesity - Riccardo Dalle Grave; Simona Calugi; Elena Centis; Marwan El Ghoch; Giulio Marchesini (Hindawi Limited, 2011)
Physical activity plays a major role in the development and management of obesity. High levels of physical activity provide an advantage in maintaining energy balance at a healthy weight, but the amount of exercise needed to produce weight loss and weight loss maintenance may be difficult to achieve in obese subjects. Barriers to physical activity may hardly be overcome in individual cases, and group support may make the difference. The key role of cognitive processes in the failure/success of weight management suggests that new cognitive procedures and strategies should be included in the traditional behavioral treatment of obesity, in order to help patients build a mindset of long-term weight control. We reviewed the role of physical activity in the management of obesity, and the principal cognitive-behavioral strategies to increase adherence to exercise. Also in this area, we need to move from the traditional prescriptive approach towards a multidisciplinary intervention.